A 10-Year Multicentre Experience of Australian Penile Fracture Repair Outcomes - Matthew Yii; Chrisdan Gan; Kirby R. Qin; Damien Bolton; Gideon Blecher (Société Internationale d’Urologie Journal, 2024)
Objectives and Methods: Penile fractures are a urologic emergency involving the rupture of the tunica albuginea of the corpora cavernosum. Geography is known to impact fracture aetiology, and higher impact aetiology is thought to predispose patients to complex trauma. To review long-term urinary and sexual outcomes following fracture repair in Australia, a retrospective analysis of data from three metropolitan hospital services over 10 years was performed. Only patients with intraoperatively confirmed fractures were included. Patients were contacted by clinicians to complete a survey, which utilised validated questionnaires, including the International Index of Erectile Function-5 (IIEF-5) and the International Prostate Symptom Score (IPSS). Perioperative data were analysed against survey responses. Results: We identified 55 confirmed penile fractures. Twenty-one patients completed questionnaire follow-ups, comprising the study cohort. The median age at the time of the injury was 44.8 years (range: 25–65). The median time from injury to questionnaire completion was 4.0 years (range: 1–10). Furthermore, 95.5% (20) of the injuries occurred during sexual intercourse. The median IIEF-5 score was 23 (range: 5–25); the median IPSS score was 5 (range: 0–22). Seven patients (33.3%) sustained a bilateral cavernosal injury, and eight (38.1%) sustained a urethral injury. Upon conducting a Mann–Whitney U test, no significant relationships were found between bilateral cavernosal injury and IIEF-5 scores (p = 0.7377) or urethral injury and IPSS scores (p = 0.5338). Conclusions: The Australian aetiology of penile fractures appears consistent with that of other Western countries, with subsequent high rates of bilateral cavernosal and urethral injuries. The long-term erectile and urinary function outcomes observed are promising. A larger prospective study would further illuminate the relationship between injury factors and outcomes, revealing information not presented herein due to study limitations relating to the cohort size and follow-up rates.